Analisis Insiden Keselamatan Pasien di Rumah Sakit Berdasarkan Pendekatan Beban Kerja dan Komunikasi - Agus Aan Adriansyah, S.KM., M.Kes.; Budhi Setianto; Nikmatus Sa'adah; Pinky Ayu Marsela Arindis; Wahyu Eka Kurniawan; Indah Lestari (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2021)
Patient safety incidents at Ahmad Yani Islamic Hospital Surabaya increased by 0.3% in 2019. If not addressed immediately, these problems can give a negative image to hospitals and patients. An error that appears and has an impact on increasing patient safety incidents, stems from a high workload and poor communication. The purpose of this study was to analyze the role of workload and communication on the occurrence of patient safety incidents in hospitals. This study uses a unit of analysis as many as 18 work units that directly provide services to patients. Participants include the head of the work unit, the person in charge of the work unit and the person in charge of the quality of the work unit with a total of 90 people. The data was obtained primarily using the instrument contained in the google form. The communication measurement tool uses the Communication Openness Measurement (COM) and the workload uses the WISN calculation. Patient safety incident data was obtained from the PMKP RS team. The analysis was carried out by means of a simple cross tabulation with interpretation using the Pareto concept. The results showed that most work units (83.3%) had a low workload, most of the work unit communication (61.1%) was not good and 33.3% of work units had a high patient safety incident rate. In the Pareto concept, the results showed that workload had no effect on patient safety incidents, while communication influenced the number of patient safety incidents. Therefore, hospitals need to fix the pattern and flow of communication as well as the need for information disclosure so that the flow of information becomes more adequate, transfer of knowledge becomes better and employee understanding of the importance of patient safety in hospitals becomes better.